ASYMMETRIC INFORMATION COST DAN HOLDING PERIODS SAHAM BIASA DI BURSA EFEK INDONESIA - Sulistyo, Sulistyo; Maulina, Vinus (Jurnal Ekonomi Modernisasi, 2010)
The aim of this study is analyze variable s influencing holding period of common stock on public firm listed in LQ 45 index, that are firms generally have good performance assessed based on both marked performance and firm fundamental, then analyzing the dominance influencing variable. This study is conducted in Indonesian Stock Exchange with population of stock listed in LQ 45 index with the total of 64 firms. The samples taking method in purposive sampling with the criteria that the firms at least listed twice in LQ45 index on the study period. The analysis method used to analyze independend variable: spread, market value, variance return, and dividend pay out ratio and dependend variable: holding period is two stage least squares multiple regression model, since there is possibility that the correlation of bid-ask spread from the current periods and bid-ask spread and holding period and holding period from the previous period for every stock take place simultaneously. The result of study showed thar, partially, bid-ask spread variable that constitutes the different value between the highest price provided paid by buyer with the lowest price offered by seller has significance positive correlation on holding period of common stock and there is inverse correlation/significance negative between variance return variable that reflect the risk rate from stock effected by fluctuation     of stock price and holding period of common stock. While simultaneously, there is not significance correlation between dependent variable and independend variable that mean bid-ask spread, market value, variance return and dividend pay out ratio can’t describe variation from hoding period variable.